PENERAPAN METODE KONTRUKTIVISTIK PADA PELAJARAN AQIDAH AKHLAK DI MTS DARUL ULUM JOGOROTO - Lailatul Ma’rufah, Nur; Faridl Darmawan, Moh.; Farid Nasrullah, M. (IMTIYAZ: Jurnal Ilmu Keislaman, 2025)
This research aims to describe the application of constructivist theory in the learning of Aqidah Akhlak at MTs Darul Ulum Jogoroto and to analyze its impact on the improvement of students' learning outcomes. The constructivist theory emphasizes the active role of students in building knowledge through interaction with the environment and meaningful learning experiences. The research method used is qualitative with a case study approach, involving observation, interviews, and documentation as data collection techniques. The research results show that the application of the constructivist learning model, which involves activities such as observing, questioning, experimenting, reasoning, and actively communicating, is able to enhance students' understanding and learning outcomes in the subject of Aqidah Akhlak. Additionally, the application of methods such as problem-based learning, discussions, and scientific learning creates an enjoyable learning atmosphere and encourages students to be independent in building knowledge. Evaluation is conducted through tests and attitude observations, covering cognitive, affective, and psychomotor domains, which show significant improvements in student learning outcomes. Thus, the application of constructivist theory is effective in improving the quality of Aqidah Akhlak learning at MTs Darul Ulum Jogoroto.